Pengaruh Model Pembelajaran Inkuiri Berbasis Outdoor Learning terhadap Pemahaman Konsep Siswa pada Mata Pelajaran IPA SD Kelas IV - Rohmawati Windasari, Siti Nur; Setiyawati, Enik (MODELING: Jurnal Program Studi PGMI, 2023)
This study aims to examine whether there is an effect of outdoor learning-based inquiry learning models on students' conceptual understanding in class IV of SDN SUKO 1. This type of research is a quantitative experiment with a one group pretest-posttest design. The sample used in class IV research was 30 students. Data collection techniques used are pretest and posttest. The data obtained had an average pretest score of 63 and a posttest score had an average of 75. The results of the nonparametric Wilcoxon test statistical data obtained the number 0.00 <0.05, it was found that there was a difference before being given treatment and after being given treatment. It can be concluded that there is an influence of outdoor learning-based inquiry learning on the understanding of the concepts of fourth grade students at SDN SUKO 1 in learning natural science about plants and their functions.